2014
DOI: 10.4161/auto.32177
|View full text |Cite
|
Sign up to set email alerts
|

Choline dehydrogenase interacts with SQSTM1/p62 to recruit LC3 and stimulate mitophagy

Abstract: CHDH (choline dehydrogenase) is an enzyme catalyzing the dehydrogenation of choline to betaine aldehyde in mitochondria. Apart from this well-known activity, we report here a pivotal role of CHDH in mitophagy. Knockdown of CHDH expression impairs CCCP-induced mitophagy and PARK2/parkin-mediated clearance of mitochondria in mammalian cells, including HeLa cells and SN4741 dopaminergic neuronal cells. Conversely, overexpression of CHDH accelerates PARK2-mediated mitophagy. CHDH is found on both the outer and inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
99
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 52 publications
5
99
0
Order By: Relevance
“…Previous studies have shown that SQSTM1 is a central player in selective autophagy by interacting with ubiquitinated cargos or binding proteins, such as KEAP1 and CHDH (choline dehydrogenase), involved in mitophagy. 20,21,24,55,56 NEDD4-mediated ubiquitination may modulate molecular structure of SQSTM1 and lead to an increase in binding affinity to the ubiquitinated cargos or the binding proteins, thus to activate mitophagic process. Currently, we know little about NEDD4-mediated ubiquitination of SQSTM1 and the ubiquitination for function of SQSTM1 in autophhagy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SQSTM1 is a central player in selective autophagy by interacting with ubiquitinated cargos or binding proteins, such as KEAP1 and CHDH (choline dehydrogenase), involved in mitophagy. 20,21,24,55,56 NEDD4-mediated ubiquitination may modulate molecular structure of SQSTM1 and lead to an increase in binding affinity to the ubiquitinated cargos or the binding proteins, thus to activate mitophagic process. Currently, we know little about NEDD4-mediated ubiquitination of SQSTM1 and the ubiquitination for function of SQSTM1 in autophhagy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pyruvate did not affect the mitophagy mediated by choline 309 dehydrogenase (CHDH), an important molecule for mitophagy [37] 310 (Fig. S5B).…”
mentioning
confidence: 99%
“…Mitophagy is part of 37 a mitochondrial quality control system that coordinates mitochondrial 38 dynamics, biogenesis, fission, and fusion; mitophagy dysfunction is 39 thus associated with human diseases [1]. Two recessive Parkinson's 40 disease (PD) genes, PINK1/PARK6 and PARK2/parkin, are key regulators 41 of mitophagy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Depolarization of the mitochondrial membrane potential stabilizes ubiquitin phosphatase and tensin homolog-induced putative kinase 1 on the outer mitochondrial membrane, and this leads to recruitment of optineurin (OPTN) and mitophagosome formation (25). Then, recruitment of the autophagic adaptor nucleoporin 62 (P62) to the damaged and ubiquitinated mitochondrial fragments leads to the clearance of mitochondrial fragments (26). Research indicates that concomitant accumulation of P62 in the mitochondrial component of mitophagosomes is indicative of insufficient mitophagy (27).…”
mentioning
confidence: 99%